2009
DOI: 10.1038/nature08486
|View full text |Cite
|
Sign up to set email alerts
|

Pten in stromal fibroblasts suppresses mammary epithelial tumours

Abstract: SUMMARY The tumor stroma is believed to contribute to some of the most malignant characteristics of epithelial tumors. However, signaling between stromal and tumor cells is complex and remains poorly understood. Here we show that the genetic inactivation of Pten in stromal fibroblasts of mouse mammary glands accelerated the initiation, progression and malignant transformation of mammary epithelial tumors. This was associated with the massive remodeling of the extra-cellular matrix (ECM), innate immune cell inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
500
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(518 citation statements)
references
References 53 publications
13
500
0
2
Order By: Relevance
“…However, FSP-Cre is known to knock down 50%-65% of floxed target genes in the mouse prostate, 44 which has been widely used to knock out a variety of target genes. 30,47 It is well documented that a low dose of estrogen can increase AR expression, prostate weight and prostatic budding in the rodent prostates, 48,49 which suggested that the physiological range of estrogens via ERs might promote prostatic branching morphogenesis and is consistent with our current studies that either loss of ERa in whole body 18 or only in stromal cells inhibit branching morphogenesis in the rodent prostates. It is well known that there are endogenous estrogens in males.…”
Section: Discussionsupporting
confidence: 90%
“…However, FSP-Cre is known to knock down 50%-65% of floxed target genes in the mouse prostate, 44 which has been widely used to knock out a variety of target genes. 30,47 It is well documented that a low dose of estrogen can increase AR expression, prostate weight and prostatic budding in the rodent prostates, 48,49 which suggested that the physiological range of estrogens via ERs might promote prostatic branching morphogenesis and is consistent with our current studies that either loss of ERa in whole body 18 or only in stromal cells inhibit branching morphogenesis in the rodent prostates. It is well known that there are endogenous estrogens in males.…”
Section: Discussionsupporting
confidence: 90%
“…20,30 FSP1 usually serves as a sensitive and specific marker for fibroblasts. 31 Recently, using FSP1 as the promoter in Cre-loxp system, Trimboli et al 32 described that Pten in stromal fibroblasts suppresses mammary epithelial tumors. And in normal mice, it has been proved that FSP1 is specific for fibroblasts by genetic and protein criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour stroma can be a reasonable place for presence of stem cells, and it is noted that the stromal microenvironment of a tumour may contribute to the malignant features of epithelial tumours. (Trimboli et al, 2009;. The biological role of ALDH1 apart from its potential role in stem cells and cellular differentiation might be another explanation for diverse effects of epithelial and stromal ALDH1 expression (Heerma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that frequency of cancer DOI:http://dx.doi.org/10.7314/APJCP.2012.13.6.2973 stem cells within breast tumours may correspond to the risk of distant metastases (Abraham et al, 2005;Glinsky et al, 2005;Trimboli et al, 2009). Due to the lack of information on distant metastases, we could not investigate its correlation with the prevalence of ALDH1+ tumour cells.…”
Section: Discussionmentioning
confidence: 99%